Views of secondary school students on ideal teacher qualifications: A phenomenological analysis - Fatma Kalkan; Emine Dağlı (International Journal of Evaluation and Research in Education (IJERE), 2021)
This research aimed to reveal the views of secondary school students on ideal teacher qualifications. For this purpose, research was carried out in a phenomenological pattern, which is one of the qualitative research methods. The study was carried out with 76 students who were studying in a secondary school in the 2017-2018 academic year. The data were obtained with the repertory grid technique and interview technique. As a result of the analysis of the data, it was seen that the qualifications of the teachers considered ideal by the participants were among the general competencies of the teaching profession. According to the results of this research, ideally, teachers are expected to provide good and fun lessons, not discriminate among students, be friendly and calm in communications with students, and ensure discipline and democracy in the classroom environment.